PEMANFAATAN ALAM SEKITAR DALAM MEMOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 03 OKU - Sendy Velya; Treny Hera; Bambang Hermansah (STKIP Subang, 2023)
ABSTRAC This study aims to find out how the use of the natural surroundings in motivating learning for fourth grade students of SD Negeri 03 OKU. This research uses a qualitative approach with descriptive methods. The subjects of this research were class IV teachers and class IV students. Collecting data in this study using observation techniques, interviews, questionnaires and documentation. The data analysis technique used is data collection, data reduction, data presentation, verification (drawing conclusions). Based on the results of the research, it can be concluded that the use of the natural surroundings can motivate students to learn science in class IV SD. Keywords: natural surroundings, student learning motivation, science subjects. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana pemanfaatan alam sekitar dalam memotivasi belajar siswa kelas IV SD Negeri 03 OKU. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek penelitian ini adalah guru kelas IV dan siswa kelas IV. Pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara, angket serta dokumentasi. Teknik analisis data yang digunakan ialah pengumpulan data, reduksi data, penyajian data, veryfication( menarik kesimpulan). Berdasarkan hasil penelitian dapat di simpulkan bahwa pemanfaatan alam sekitar dapat memotivasi belajar siswa pada pembelajaran IPA kelas IV SD. Kata kunci : alam sekitar, motivasi belajar siswa, mata pelajaran IPA.